Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Des femmes respectables : classe et genre en milieu populaire - Skeggs, Beverley (Agone, 2015)
La matière première de ce livre est une série d'entretiens menés par Beverley Skeggs avec quatre-vingt-trois jeunes femmes issues de la classe ouvrière anglaise, inscrites à une formation d'aide à la personne et travaillées par leur propre respectabilité. Abordant leur rapport à la sexualité, à la classe ou au féminisme, cet ouvrage vient apporter un prolongement essentiel aux travaux de Pierre Bourdieu et de Paul Willis.
Keywords: 1900-1999; 1980-1989; 1990-1999; analyse de discours; angleterre; approches et analyses; care; classe ouvrière; classe sociale; cours; cultural studies; cycles supérieurs; discipline; ethnographie; europe; fem7000; fémininité; féminisme marxiste; histoire et politique; point de vue situé; périodes historiques; rapports sociaux de sexe; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sciences sociales; sexualité; sociologie; thématiques; épistémologie

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

‘Psy’, ‘coach’ et travail dans ‘l'entreprise du couple’: les femmes en première ligne dans Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle - Jonas, Irène (Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle, 2007)
Avec les revendications féministes, la famille a connu de nombreuses et profondes transformations au cours de ces dernières années. Elles ont pourtant été inégalement réalisées et, lorsqu’elles le furent, elles n’ont pas pour autant aplani toutes les difficultés. Ces textes traitent de l’accouchement, de l’avortement, de la contraception, du divorce, du mariage et de la recomposition familiale, des relations de couple, aux quatre coins de la francophonie: le Brésil, la France, la Grèce, le Sénégal, la Suisse et le Québec. Situations forcément différentes et pourtant questions communes susceptibles d’élargir la réflexion transfrontalière face à une institution, la famille, partout remise en cause, avec les premiers balbutiements de l’égalité des sexes. Textes de Fatou Binetou Dial, Nikoletta Chardalia, Irène Jonas, Françoise Le Borgne-Uguen, Ana Liesi Thurler, Sylvie Perrier, Éliane Perrin et son équipe, Isabelle Puech, Catherine Pugeault-Cicchelli, Lucia Scavone, Carmen Susana Tornquist, Hélène Trellu et une introduction de Marie-Blanche Tahon.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; brésil; care; corps; cours; discipline; france; francophonie; grèce; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; suisse; sénégal; thématiques; travail; travail social; trs1205

La santé est politique - Vuille, Marilène; Rey, Séverine; Fussinger, Catherine; Cresson, Geneviève (Nouvelles Questions Feministes, 2006)
Keywords: 1900-1909; 1900-1999; 1970-1979; 1980-1989; 1990-1999; allemagne; approches et analyses; care; corps; cours; discipline; europe; france; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail